Latin American Trade Policies in the 1970's: Reply - Schydlowsky, Daniel M. (Quarterly Journal of Economics, 1975)
Journal Article Latin American Trade Policies in the 1970's: Reply Get access Daniel M. Schydlowsky Daniel M. Schydlowsky Boston University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 3, August 1975, Pages 487–489, https://doi.org/10.2307/1885269 Published: 01 August 1975